A 22-year study to evaluate disparities in place of death in the United States using the CDC WONDER database for intracerebral hemorrhage - Lade, Ananya; Alpizar, Kevin G. Chaverri; Nachu, Amrutha; Goel, Ramita; Pansuriya, Jaymin; Pillikunte Doddareddy, Navya; Saravanan, Abirami (International Journal of Research in Medical Sciences, 2024)
Background: Interpretation of data collected from the CDC WONDER database and analysis of disparities in places of death for those patients diagnosed with intracerebral hemorrhage (ICH) in the United States from 1999 to 2020. Our research intends to uncover important insights into potential differences in end-of-life care for patients suffering from ICH and to provide solicited care during this crucial time. Methods: We conducted an epidemiological study in which all patient-specific demographics were extracted from the CDC WONDER database evaluated for disparities in place of death, and compared based on variables. The odds ratio was also calculated. Qualitative data was expressed in percentage and proportion, whereas statistical analysis was done using R programming software. Results: Data of 18,783,791 ICH deaths was aggregated. Data explained that patients in the 85+ age group are the most likely to die at home, and this particular age group also has seen the highest number (1,941,657) of fatalities in home or hospice and the highest number (4,937,395) of fatalities in medical or nursing facilities. Male patients in the 55–64 age group were most likely to die at home or hospice, whereas female patients in general were most likely to die in medical or nursing facilities. West census region patients were 1.424 times more likely to die at home or hospice, this number being the highest of all regions. Conclusions: Home or hospice mortality trend in patients with ICH, within a 22-year period, increased significantly, specifically in white male patients ages 85 and older from the west rural region.